Central and Peripheral Analgesic Activities of Aqueous Extract of Centella Asiatica (AECA) Leaves in Rats and Mice (Sciences of Pharmacy, 2023)
The demand of herbal based medicines are increasing all over the world and the focus on plant research has increased. Centella asiatica (CA) is a medicinal herb used in traditional medicine as remedy for a variety of diseases. It is widely used in Ayurvedic medicines. The present study evaluated the Analgesic Activity of Aqueous Extract of the leaves of Centella asiatica (AECA). Acute oral toxicity test was performed according to Organization for Economic Cooperation and Development, 2008 (OECD) guidelines. The tail flick method and glacial acetic acid-induced writhing tests were used to study the central and peripheral analgesic activities of AECA, respectively. AECA (200mg/kg) produced significant analgesia in both central and peripheral mechanisms compared to the control. The maximal analgesic effect was observed after 90 minutes of drug administration in the tail-flick method. In the glacial acetic acid-induced writhing test, AECA (200 mg/kg, p.o) produced a significant decrease (71.07%) in the number of writhes (p<0.01) when compared to the control. Therefore, CA can be a very promising herbal-based medicine for treatment of various painful conditions. Further investigations are needed to determine the precise mechanism and site of action of AECA.